Theological nomadism. Poet(h)ics and politics of the uncanny sublime in Delimir Rešicki’s poetry - Vuković, Tvrtko (Poznańskie Studia Slawistyczne, 2011)
The poetry written by the Croatian poet Delimir Rešicki is associated with some of the more influential concepts of the Romantic poets. The paper analyzes the method by which Rešicki develops Christlike motives as a model of shaping the authorial concept and comprehending the poetic identity associated with the idea of a (divine) Genius. The focus is therefore placed on two textual strategies: stylizing the lyrical subject as an urban model and representing the idea of nomadism as the predominant existential form. The phrase “theological nomadism” is hereby used to relate the convergence of Rešicki’s lyrical poetry and Romanticism to some of the recent ethical and political debates in the field of theory.